Toxic hepatitis: literature review - Costa Matos, Luís (2005)
We consider toxic hepatitis to be liver injury caused by chemical or pharmacological agents and we feel that it should be considered in the initial differential diagnosis of liver disease. The authors present a literature review of this subject, including hepatic drug metabolism physiology, diagnostic criteria, laboratory and clinical presentations, and a review of the classic hepatotoxic drugs, as well as newer drugs, excipients and “natural” products, that sometimes cause hepatic damage.